Progress in research on the role of exosomal miRNAs in the diagnosis and treatment of cardiovascular diseases - Xu, Jinyu; Wang, Weitie; Wang, Yong; Zhu, Zhicheng; Li, Dan; Wang, Tiance; Liu, Kexiang (Frontiers in Genetics, 2022)
Cardiovascular diseases are the most common diseases threatening the health of the elderly, and the incidence and mortality rates associated with cardiovascular diseases remain high and are increasing gradually. Studies on the treatment and prevention of cardiovascular diseases are underway. Currently, several research groups are studying the role of exosomes and the biomolecules incorporated by exosomes in the prevention, diagnosis, and treatment of clinical diseases, including cardiovascular diseases. Now based on the results of published studies, this review discusses the characteristics, separation, extraction, and identification of exosomes, specifically the role of exosomal miRNAs in atherosclerosis, myocardial injury and infarction, heart failure, aortic dissection, myocardial fibrosis, ischemic reperfusion, atrial fibrillation, and other diseases. We believe that the observations noted in this article will aid in the prevention, diagnosis, and treatment of cardiovascular diseases.